Estudo de alterações em artérias de ratos espontaneamente hipertensos após o tratamento com bloqueadores dos receptores da angiotensina II usando microscopia de raios X de baixa energia com radiação síncrotron - Oliveira, Arissa Pickler (2019)
Hypertension is one of the major public health problems worldwide due to its strong impact on cardiovascular (CV) morbidity and mortality. The hypertension can cause damage in target organs such as arteries, kidneys, and the central nervous system. The main forms of hypertension treatment include non-drug actions and also the use of antihypertensive drugs in order to reduce blood pressure (BP) and prevent CV and renal outcomes. Among the antihypertensive drugs used to regulate BP are the angiotensin II receptor blockers (ARBs). The efficacy in reducing BP of this drug class is widely recognized in the literature. However, its efficiency to protect organs that may be affected is still poorly explored. The aim of this work was evaluate, at an elemental level, the effects of the BRAs, losartan and olmesartan in the coronary and aortic arteries of hypertensive rats. The Low Energy X-Ray Fluorescence (LEXRF) technique was used to obtain elemental distribution maps, allowing semiquantitative analyzes of O, Na, Mg, Fe, Cu and Zn elements in coronary and aortic samples. The results demonstrate that despite the antihypertensive agents used belong the same class, their capacities to inhibit chemical and structural changes in coronary and aortic arteries caused by hypertension are differents.